TSH Regulates Pendrin Membrane Abundance and Enhances Iodide Efflux in Thyroid Cells - Pesce, Liuska (Endocrine Society, 2012)
Thyroid hormones are essential for normal development and metabolism. Their synthesis requires transport of iodide into thyroid follicles. The mechanisms involving the apical efflux of iodide into the follicular lumen are poorly elucidated. The discovery of mutations in the SLC26A4 gene in patients with Pendred syndrome (congenital deafness, goiter, and defective iodide organification) suggested a possible role for the encoded protein, pendrin, as an apical iodide transporter. We determined whether TSH regulates pendrin abundance at the plasma membrane and whether this influences iodide efflux. Results of immunoblot and immunofluorescence experiments reveal that TSH and forskolin rapidly increase pendrin abundance at the plasma membrane through the protein kinase A pathway in PCCL-3 rat thyroid cells. The increase in pendrin membrane abundance correlates with a decrease in intracellular iodide as determined by measuring intracellular (125)iodide and can be inhibited by specific blocking of pendrin. Elimination of the putative protein kinase A phosphorylation site T717A results in a diminished translocation to the membrane in response to forskolin. These results demonstrate that pendrin translocates to the membrane in response to TSH and suggest that it may have a physiological role in apical iodide transport and thyroid hormone synthesis.